Can vegetation clearing operations and reprofiling of bars be considered as an ecological restoration measure? Lessons from a 10‐year vegetation monitoring program (Loire River, France). Issue 3 (13th May 2022) - Janssen, Philippe; Chevalier, Richard; Chantereau, Michel; Dupré, Rémi; Evette, André; Hémeray, Damien; Mårell, Anders; Martin, Hilaire; Rodrigues, Stéphane; Villar, Marc; Greulich, Sabine
Abstract : Maintenance operations in regulated rivers are often implemented as preventive measure to maintain wide, smooth channels and to limit the risk of flooding. By clearing vegetation, removing roots and lowering sediment bar elevation, these works can recreate pioneer habitats and related plant communities. Using a before‐after‐control‐impact design with monitoring of riparian vegetation over 10 years, we evaluated the effects of fluvial maintenance works on plant richness and composition in an island complex located in a Nature Reserve along the Middle Loire River. Our results showed that artificial rejuvenation operations had a significant short‐term negative effect on richness. However, in the few years following the work, the riparian communities established on the rejuvenated island became more diverse, with a large proportion of annual plants, contributing to the increased species pool of the Nature Reserve. In addition, we found that temporal changes in species richness were strongly influenced by hydrological conditions, with a peak in biodiversity observed during prolonged summer low water. This highlights the importance of considering flow variations to more accurately assess the ecological benefit of restoration operations on riparian vegetation. Overall, as successional stages were more advanced at the island complex scale, fluvial maintenance works have allowed the recreation of sandy pioneer habitats exposed to flooding. These habitats have promoted the establishment of species‐rich communities without favoring the installation of invasive alien species. From this view, the maintenance works have increased the mosaic of habitats within the Nature Reserve and have restored environmental conditions favorable to early‐successional species.